Vibration measurement by means of digital speckle correlation - Li L. Lin; Gubarev F. A. Fedor Aleksandrovich; Klenovsky M. S. Miron Stanislavovich; Bloshkina A. I. Alena Igorevna (2016, 2016)
Title screen